Efektivitas Penerapan Permainan Edukasi Berbasis Quizizz terhadap Peningkatan Kemandirian Belajar dan Sikap Ilmiah - Ekaputra, Firdiawan; Sungkono (Epistema, 2025)
This study has two main objectives, namely: (1) to analyze the effectiveness of increasing student learning independence after the implementation of learning media in the form of Quizizz-based educational games, and (2) to assess the effectiveness of increasing students' scientific attitudes through the use of learning media in the form of Quizizz-based educational games. The research subjects consisted of students in Class A of the Chemistry Education Study Program at the University of Jambi who took the Chemistry Learning Media course in the 2022/2023 academic year. The type of research used was an experiment with a single group design using a pretest-posttest scheme. Data collection on learning independence and scientific attitudes was conducted using a questionnaire instrument. The collected data were then analyzed using a paired samples t-test to determine the differences before and after the use of Quizizz-based educational games as learning media. The results showed that: (1) there was a significant increase in learning independence after students used Quizizz-based educational games as learning media, and (2) there was also a significant increase in students' scientific attitudes after the application of Quizizz-based educational games as learning media.